India : Financial Sector Assessment Program-Detailed Assessments Report on IAIS Insurance Core Principles. (IMF Staff Country Reports; Country Report ;, 2013)
This paper discusses key findings of the assessment of India's compliance with the International Association of Insurance Supervisors Insurance Core Principles (ICP). Indian Regulatory and Development Authority (IRDA) has so far decided that India is not yet ready for a full transition to cutting-edge international approaches owing to informational and skills shortages and a continuing lack of international consensus. Certain prudential ICPs come under this heading, and IRDA will need to augment its resources in its core supervisory departments if it is to introduce a rigorous corrective action and enforcement regime built on a risk-based approach to the capital and operational management of insurers.